Risk-based energy management : DC, AC and hybrid AC-DC microgrids - Nojavan, Sayyad; Shafieezadeh, Mahdi; Ghadimi, Noradin (Academic Press, 2020)
Risk-Based Energy Management: DC, AC and Hybrid AC-DC Microgrids defines the problems and challenges of DC, AC and hybrid AC-DC microgrids and considers the right tactics and risk-based scheduling to tackle them. The book looks at the intermittent nature of renewable generation, demand and market price with the risk to DC, AC and hybrid AC-DC microgrids, which makes it relevant for anyone in renewable energy demand and supply. As utilization of distributed energy resources and the intermittent nature of renewable generations, demand and market price can put the operation of DC, AC and hybrid AC-DC microgrids at risk, this book presents a timely resource. --